Synchronizing the Regional Boundary Dispute Resolution - Naswar; Maskun; Ilmar, Aminuddin; Achmad (International Journal of Psychosocial Rehabilitation, 2020)
The issue of regional boundaries does not become an absolute requirement that must be met before being legalized as a new autonomous region. Therefore, the map made in the appendix to the Law on Regional Formation (UUPD) also means merely a clue to the location of the region that the territory exists among other regions, or is just a differentiator between one region and another, no more. This problem is one of the triggers for conflict with regional boundaries. The purpose of this study is to synchronize Law No. 22 of 1999, Law No. 32 of 2004 as well as Law No. 23 of 2014) and their derivative laws, particular the Ministry of Internal Affairs Decree (Permendagri) No. 1 of 2006 which has been replaced by Permendagri No. 76 of 2012, then replaced again with Permendagri No. 141 of 2017 concerning Affirmation of Regional Boundaries. Those laws and Permendagri are exercised in the West Sulawesi as the site of the study. The results of the study show that the synchronization of the regional boundaries must be done by adoption the bottom-up concept. In the context of the Province of West Sulawesi, the delimitation stage of the area boundaries has not been followed by the definition of a clear point and boundary line in the map of Law No. 26 of 2004.